On Function of Herajo Sekki - Takahashi, Akira (Nihon Kokogaku(Journal of the Japanese Archaeological Association), 2007)
Herajo sekki (spatula type stone tool), a type of stone tool in the Jomon period, was named after characteristics of its shape, and is classified as a tool for digging earth or for processing hide. As analysis on use marks has being accumu-lated in recent years, it is now considered a tool for processing hide by whittling. Soki (end scraper) which coexisted with herajo sekki, , is also a tool for processing hide, however, its operation method is different as it is used for scraping. It seems highly probable that Jomon culture had at least two types of hide processing tools, and different tools were used according to the purpose of hide processing.